Presence, localization and morphology of TELOCYTES in developmental gonads of fishes - Mazzoni, Talita Sarah [UNESP]; Viadanna, Renan Ribeiro [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Wiley, 2019)
Telocytes are a new defined type of interstitial cells, considered as a stem cell, with very long and thin cytoplasmic extensions. They are present in the vertebrates, and may participate in tissue remodeling. In fish, during gonadal development, the events that culminate with the germinal epithelium formation are well known. However, the interstitial compartment remains poorly explored, although it may have a great contribution to the morpho-functional changes that occur in the gonad. As in other organisms, in fish, the interstitium consists especially of connective tissue elements. However, until now, there are no reports of the presence and the action of the telocytes in the connective tissue of gonads of fish. Thus, this study aimed to detect the presence, localization and morphology of telocytes during the gonadal development of several species of fish. The gonads were analyzed by light microscopy, transmission electron microscopy and immunohistochemistry for localization of CD34, Vimentin, and metalloproteinases. The presence of two proteins characteristics of mesenchymal cell was detected in cells of the gonads of all species. In addition, they presented a typical morphology of telocytes, showing cellular extensions. Gonadal telocytes also presented positive response to metalloproteinases. In mammals, telocytes can undergo de-differentiation contributing to the reorganization of the extracellular matrix. This role may be performed by the metalloproteinases detected here. The detection of Vimentin and CD34 in the same cellular type, associated with its morphological characteristics, allows us to conclude that some interstitial cells in Teleostei are considered telocytes, identical to the ones already described in mammals and other vertebrates.
Keywords: gonadal remodeling; interstitial cell; Teleostei; telocyte